The Effect of Alfalfa Meal Supplementation in Concentrate on Feed Digestibility of Ettawa Crossbred Goat! - Hanim, Chusnul (2017)
This research was conducted to determine feed digestibility of Ettawa Crossbred (EC) goat fed concentrate supplemented with alfalfa meal. Eleven EC goats, age 1.5 to 2.5 years, initial body weight 32.2 to 50.5 kg and milking periode 2 to 3.5 months, fed with forages consisted of king grass, Gliricidia maculata and concentrate supplemented with alfalfa meal by 0%, 2.6%, and 5.1% (dry matter basis). The proportion of forages and concentrate was 50:50 (dry matter basis). The diet and water was introduced ad libitum. Collected data were consumption of dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), ether extract (EE), nitrogen free extract (NFE), and total digestible nutrients (TDN) as well as digestibility of DM, OM, CP, CF, EE, and NFE. The data were analyzed variance using one way design, the differences between mean continued by Duncan’s New Multiple Range Test (DMRT). The result showed that the supplementation of alfalfa meal in concentrate up to 5.1% had no effect on feed consumption. However, the supplementation of alfalfa meal in concentrate up to 5.1% increased the digestibility of DM 9.3% (78.34% vs 71.65%), OM 8.8% (79.44% vs 72.96%), CF 24.8% (81.95% vs 65.64%), EE 28.5% (88.74% vs 69.03%) compared with control, but didn’t affect digestibility of CP and NFE. It could be concluded that the supplementation of alfalfa meal up to 5.1% increased the nutrient digestibility, and it could metthe nutrient requirement of EC goat.